The challenge of man's future: an inquiry concerning the condition of man during the years that lie ahead - Brown, Harrison (New York, Viking Press, 1954)
The book examines man's past and present and,on the basis of the clues derived from such a study ,to examine his future
obn 23/01/2019
Loans
Keywords: Human geography